An Eddy-current based RRR measurement technique for SRF cavities. (April 2019) - Sagar, P; Karunanithi, R; Hassan, H K; Akber, K; Girish, P S; Chandran, S; Lakshmi, EDA
Abstract: Residual Resistivity Ratio (RRR) is an important parameter which is used to determine the purity and thermal conductivity of Niobium (Nb) utilized for fabrication of Superconducting Radio Frequency (SRF) cavities. The usual 4-wire electrical resistance measurement method is destructive in nature and produces a non-local (average) measurement of the electrical conductivity. The present work utilizes Printed Circuit Board (PCB) based planar inductor as sensing element. The impedance variation of the sensing element in the presence of a conducting metal (Nb), is used to determine the conductivity of the Nb target. A generalized equation for RRR is proposed in terms of parameters 'a' and 'b' associated with the sensing coil. The measurement method is experimentally verified by utilizing samples of Nb of known RRR values. The sensor parameters ('a' and 'b' ) are also established for cryogenic conditions. Errors in measurement, accuracy and repeatability of measurements down to 4.2 K are reported.